Implementation of Print Package at Mobile Service Point Innovation for Population Documents - Hartono, Selamat; Ritonga, Syafruddin; Batubara, Beby Masitho (Journal La Sociale, 2025)
This study investigates the implementation of the "PAK CEPAT YANLING" (On-the-Spot Printing Mobile Service) innovation for civil documentation at the Department of Population and Civil Registration in Serdang Bedagai Regency. It aims to assess the effectiveness of this initiative and identify the factors hindering its implementation. Using George C. Edward III's implementation theory, this research employs a qualitative descriptive method with data collected through observation, interviews, documentation, and literature review. The findings reveal that the implementation of "PAK CEPAT YANLING" has been successful based on four indicators: communication, resources, disposition, and bureaucratic structure. However, challenges persist, including low public awareness of the importance of civil documentation, insufficient socialization of requirements, and limited community interest in managing civil documents. The study concludes that while the initiative demonstrates notable progress, addressing these barriers is essential for maximizing its impact and ensuring sustainable success.